Politics of Legal in Nominee Agreement And Its Practice In Indonesia - SUPARJI, SUPARJI (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
This study aims to examine the legal politics of nominee agreement in Indonesia. The research method used is normative juridical, which conceptualizes the law as what is written in the legislation or the law as a rule or norm that is a benchmark of human behavior that is considered appropriate. This type of legal research is carried out by examining secondary data in the field of law as library data using deductive thinking methods. The results stated that there are no specific rules that override or provide other possibilities related to the issue of absolute ownership of shares by shareholders registered in the register of shareholders of a limited liability company. The unauthorized nominee of agreement in Indonesia is prohibited. The prohibition on nominee agreement is clearly stated in Law No. 25 of 2007 concerning investment. In fact, nominee agreement has grown and developed in the community, due to community needs. Establishment of nominee agreements in practice can be categorized into the formation of direct nominee agreements, namely by directly making agreements between those who affirm that ownership of shares in a company is limited to and on behalf of others. Thus, the legal profession such as notary, legal consultant and lawyer in this case must provide legal counseling, and participate in supervisory duties. As a profession, it should keep the professional code of ethics instead of making unauthorized nominee by making a nominee agreement.